2022
DOI: 10.3390/ijerph192416637
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Media Marketing on Consumer Engagement in Sustainable Consumption: A Systematic Literature Review

Abstract: Social media have progressed drastically in building successful consumer engagement both in brand building and sustainable consumption. This paper is a review of the articles concerning the influence of social media marketing on consumer engagement in sustainable consumption practices published over the last 8 years. We follow the PRISMA technique as a methodological approach. The review investigates 70 empirical research articles published between 2014 and 2022. A total of 70% of the reviewed articles were pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 88 publications
(69 reference statements)
0
4
0
3
Order By: Relevance
“…Consumer decisions have a direct impact on nutrition and sustainability results, both of which are impacted by the type and amount of money spent and the diversity of food available ( 22 ). Also, consumers are developing more and more different behaviors as a direct consequence of technology impact and social media communications ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Consumer decisions have a direct impact on nutrition and sustainability results, both of which are impacted by the type and amount of money spent and the diversity of food available ( 22 ). Also, consumers are developing more and more different behaviors as a direct consequence of technology impact and social media communications ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the general concepts and topics covered by PRISMA are relevant for any systematic review, not only for those aimed at summarizing the benefits and harms of a health intervention [ 37 ]. PRISMA has shown that the quality of reports and methodologies improved significantly in many journals [ 38 ] and facilitated the readability and traceability of information [ 39 ]. Another benefit of its use is an improvement in the details of study designs, results, and measurements [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, a survey by Vrontis et al (2021) explores the current themes and research gaps in social media influencer marketing. Besides, Bryła et al (2022) focus on the impact of social media marketing on consumer engagement. A study in 2022 conducted advanced social media marketing strategies and background research on social media marketing in various contexts (Swathi & Linus, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%